"Melville and His Medusae: A Reading of _Pierre_" - Šesnić, Jelena (Array, 2005)
In this reading of H. Melville's novel _Pierre_ (1852) the author examines two principal plot lines, the sentimental and the Bildungsroman. Drawing on feminist, new historicist and cultural theory reading models, such as proposed by R. Girard and elaborated by E. K. Sedgwick, notably in the model of the triangulation of homosocial desire, the article questions the capacity of the sentimental plot to sustain the weight of the mythic implications attributed to femininity in the novel undermined by Melville's shift in focus to the formation of his hero, Pierre. The story of hero's individuation as a model of nineteenth-century pre-Civil War masculinity is shown to be heavily dependent, even as it masks and repudiates these links, on salient cultural/mythic conceptualizations of the feminine, here reflected through the Gorgon myth. In the novel women characters range from the overpowering mother to the angelic, submissive, but ultimately entrapping virgin, to the revolutionary, menacing, Medusa-type of woman. All these female types in fact are subsidiary to the formation of male identity and are subject to the circulation of masculine desires, and a product of masculine projections. Their mythic import fixes and circumscribes their meaning and potential rather than endowing them with cultural power.